2017
DOI: 10.1080/09546634.2017.1364691
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of topical protection from ultraviolet radiation exposure: a critical review on the juxtaposition of the benefits and risks involved with the use of chemoprotective agents

Abstract: Solar ultraviolet (UV) radiation exposure is known to cause inevitable damage to human skin via different mechanisms which include disruption of genetic material and generation of free radicals. In the ever emerging field of photoprotective agents, there have been constant endeavors to uphold the standards for optimum protection from solar UV-induced damages which include alarming conditions ranging from severe keratosis to malignant transformation of skin cells. Out of the various methods available for photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 97 publications
0
7
0
1
Order By: Relevance
“…ABTS Á+ free radicalscavenging assay. 2,2 0 -azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS Á+ ) free radical-scavenging assay was conducted using the adapted method described by Bora et al (26) and Konda et al (27). A 7 mM ABTS and 2.45 mM K 2 S 2 O 8 both in aqueous solution were allowed to react in a ratio of 1:1 (v/v) in the dark for 12-24 h to generate ABTS Á+ stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…ABTS Á+ free radicalscavenging assay. 2,2 0 -azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS Á+ ) free radical-scavenging assay was conducted using the adapted method described by Bora et al (26) and Konda et al (27). A 7 mM ABTS and 2.45 mM K 2 S 2 O 8 both in aqueous solution were allowed to react in a ratio of 1:1 (v/v) in the dark for 12-24 h to generate ABTS Á+ stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…The limitation of perfect sunscreen use is that it may impair vitamin D synthesis [15] (with studies stating that sun protection factor (SPF) 15 application can reduce it up to 98% [35]), triggering some authors to express an urgent need to evaluate the long-term effect of recommending strict sun avoidance and extensive use of sunscreens in Caucasian populations [6].…”
Section: Sunscreens and Preventive Sun Avoidance As A Potential Part ...mentioning
confidence: 99%
“…However, some studies have observed that this vitamin D synthesis impairment by sunscreens is inconclusive and may not be significant in real-world conditions [35,36], though there have been few trials of the high sun protection factor sunscreens that are currently recommended widely [37].…”
Section: Sunscreens and Preventive Sun Avoidance As A Potential Part ...mentioning
confidence: 99%
“…Chemical filters with limited photostability can produce toxic photoproducts, the emission of light with a larger wave length is possible. It is debated whether there is a skin tumor risk and other unwanted side effect with this type of chemical filters [9]. It is important to remember a contemporary review [10] regarding the neurotoxicity of several organic chemical filters and two allowed physical filters (zinc oxide and titanium dioxide).…”
Section: Topical Photoprotection: Current Statusmentioning
confidence: 99%